Pelaksanaan PBL dalam Meningkatkan Capaian Pembelajaran Matakuliah Pemberdayaan Komunitas Adat Terpencil TA. 2023/2024 Ilmu Kesehatan Masyarakat FKIK Universitas Jambi - Asparian, Asparian; Sitanggang, Hendra Dhermawan; Ibnu, Ismi Nurwaqiah; Hubaybah, Hubaybah; Reskiaddin, La Ode (Jurnal Akademika Baiturrahim Jambi, 2025)
Learning Innovation Research with the title "The Influence of the Application of the Problem Based Learning (PBL) Learning Model on Learning Outcomes in the Remote Indigenous Community Empowerment Practices (KAT) Even Semester 2023/2024 Academic Year Jambi University Public Health Study Program" is the application of the Problem Based Learning method (PBL) in courses taught by researchers. This research design used Quasi Experimental on 114 students in 3 groups and different locations. Students are fully involved in every stage of problem analysis, determining priority problems, preparing activity plans, implementing activities, monitoring and evaluating. Students are given the freedom to explore, assess, interpret, synthesize various problems through primary and secondary data, then a work plan is created to solve the problems found. Lecturers who teach courses have the freedom to develop the learning process in class and outside the classroom. Course Learning Achievement (CPMK) is measured using the T-Test model analysis technique (Different test, Pre and Post-Test). The final result of this research is that students are able to improve their problem analysis skills, determine priority problems, find solutions to existing problems, develop organizational management, time management and research skills. Increasing active group participation, the ability to lead work teams and critical thinking in students will deliver Graduate Learning Outcomes (CPL).